2021
DOI: 10.3389/fpsyg.2021.726621
|View full text |Cite
|
Sign up to set email alerts
|

To Live or Die: What to Wish at 100 Years and Older

Abstract: Previous research has shown that will to live is a strong predictor for survival among older people, irrespective of age, gender, and comorbidities. However, research on whether life at age 100 is perceived as worth living is limited. The available literature has presented evidence for good levels of positive attitudes and life satisfaction at such an advanced age, but it has also suggested that a longing for death is common. This study aimed to add to the existing data on this matter by exploring centenarians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Among the centenarians, reluctant factors for living longer are reportedly annoyance, uselessness, loss of meaning, disconnection and loneliness. 24 Willingness of PoD should be considered in terms of these views. Moreover, to avoid unwanted transportation to the hospital, advanced care planning would also be necessary for healthcare providers and care givers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the centenarians, reluctant factors for living longer are reportedly annoyance, uselessness, loss of meaning, disconnection and loneliness. 24 Willingness of PoD should be considered in terms of these views. Moreover, to avoid unwanted transportation to the hospital, advanced care planning would also be necessary for healthcare providers and care givers.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings highlight the need for healthcare provisions and policies to enhance support for EoLC at preferred PoD, which include homes and home‐like environments, such as nursing homes. Among the centenarians, reluctant factors for living longer are reportedly annoyance, uselessness, loss of meaning, disconnection and loneliness 24 . Willingness of PoD should be considered in terms of these views.…”
Section: Discussionmentioning
confidence: 99%
“…Longevity is celebrated in various cultures, and many oldest-old individuals continue to live with good psychosocial well-being despite their physical and functional impairment, especially when adequate family support is available (Araújo et al, 2021;Cho et al, 2012;Wong et al, 2014). Providing care to these oldest-old individuals can be physically and mentally exhausting due to the vicissitudes and rapid deterioration of their health.…”
Section: Preprint Version 30 Th June 2023mentioning
confidence: 99%
“…Empirical findings highlight that when health and autonomy are of high personal importance and illness and dependency are feared, desired lifetimes are often lower ( Araújo et al, 2021 ; Brandão et al, 2019 ; Ekerdt et al, 2017 ; Karppinen et al, 2016 ; Rupprecht, Martin, & Lang, et al, 2022 ). In these studies, a reluctance of becoming a burden to others was reported by participants as one of the reasons why they would not be willing to live very long lives.…”
Section: Importance Of Health Autonomy and The Fear Of Becoming A Burdenmentioning
confidence: 99%
“…Becoming a burden to others may thus be a threat to older individuals with a more limited time perspective who strive to maintain emotional balance. Consequently, if conditions to not become a burden to others, who may then need to engage in caregiving duties, are no longer warranted, individuals hesitate in wishing for longer years of life ( Araújo et al, 2021 ; Karppinen et al, 2016 ). Hence, for those who fear becoming a burden and to whom health is personally important, willingness for longer lives under impairment conditions should be reduced.…”
Section: Importance Of Health Autonomy and The Fear Of Becoming A Burdenmentioning
confidence: 99%